Catalytic Asymmetric Aziridination of Benzhydryl Imines and Diazoacetate Esters with BOROX Catalysts from 3,3′-Disubstituted VANOL Ligands - Guan, Yong; Lu, Zhenjie; Yin, Xiaopeng; Mohammadlou, Aliakbar; Staples, Richard J.; Wulff, William D. (Synthesis, 2020)
This work details the synthesis of 22 new chiral VANOL ligands that differ by the nature of the substituent in the 3- and 3′-positions of the ligand. These ligands were incorporated into boroxinate catalysts that were used to screen the catalytic asymmetric aziridination of benzhydryl imines with ethyl diazoacetate. Each catalyst was screened in the reaction of imines generated from benzaldehyde and cyclohexanecarboxaldehyde and some with 4-nitro- and 4-methoxybenzaldehyde. In addition, the first report of the effect of the ester substituent of the diazoacetate ester on the asymmetric induction in these aziridination reactions is presented. The first X-ray structure of a boroxinate catalyst generated from a VANOL-derived ligand is also reported.
Keywords: VANOL; asymmetric catalysis; aziridines; BOROX catalysts; imines